Antitrust in Innovative Industries - Segal, Ilya; Whinston, Michael D (American Economic Review, 2007)
We study the effects of antitrust policy in industries with continual innovation. Antitrust policies that restrict incumbent behavior toward new entrants may have conflicting effects on innovation incentives, raising the profits of new entrants, but lowering those of continuing incumbents. We show that the direction of the net effect can be determined by analyzing shifts in innovation benefit and supply, holding the innovation rate fixed. We apply this framework to analyze several specific antitrust policies. We also show that, in some cases, the tension does not arise, and policies that protect entrants necessarily raise the rate of innovation. (JEL K21, L13, L14, L40, O30)